Notes about Urea - Velásquez, Manuel A. (1918)
Urea, molecular = 60 weight is considered to justice as the main product of protein metabolism and as the most interesting of the nitrogenous constituents of the urine and the most important too, because it contains 45% of nitrogen and taken to it 85 to 90% of the total nitrogen in the urine. This concept helps to affirm the importance of urea, the fact that almost 90% of the nitrogen introduced into the economy, food is eliminated in the urine in the form of urea.